2012
DOI: 10.1002/ls.1188
|View full text |Cite
|
Sign up to set email alerts
|

Effects of viscosity‐pressure dependency on the non‐Newtonian squeeze film of parallel circular plates

Abstract: On the basis of the Barus experimental research, the viscosity of an incompressible lubricant grows exponentially with its pressure. Therefore, the squeeze film issues between parallel circular plates lubricated with a non‐Newtonian couple‐stress fluid are reexamined in the present study by considering the effects of viscosity‐pressure dependency. According to the results, the influences of viscosity‐pressure dependency raise the load capacity and lengthen the approaching time of the plates. Numerical results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…According to the study by Gould [20], the variation of viscosity with pressure is important especially in the high pressure squeeze films. Lin et al [21,22] analyzed the theoretical study of combined effects of non-Newtonian couple stress rheology and viscosity pressure dependency (VPD) in the sphere plate squeeze film and squeeze film circular plates. Reddy et al [23] predicted the effect of viscosity variation on the squeeze film performance of narrow hydrodynamic journal bearings with couple stress fluid.…”
Section: Advances In Tribologymentioning
confidence: 99%
See 1 more Smart Citation
“…According to the study by Gould [20], the variation of viscosity with pressure is important especially in the high pressure squeeze films. Lin et al [21,22] analyzed the theoretical study of combined effects of non-Newtonian couple stress rheology and viscosity pressure dependency (VPD) in the sphere plate squeeze film and squeeze film circular plates. Reddy et al [23] predicted the effect of viscosity variation on the squeeze film performance of narrow hydrodynamic journal bearings with couple stress fluid.…”
Section: Advances In Tribologymentioning
confidence: 99%
“…Recently, Lin et al [22] have studied the effects of viscosity-pressure dependency on the non-Newtonian squeeze film of parallel circular plates with an assumption that bearing surfaces are smooth. Hence the main objective of this paper is to study the effects of surface roughness on the couple stress squeeze film lubrication between circular plates by considering the pressure dependent viscosity variation which has not been studied so far.…”
Section: Advances In Tribologymentioning
confidence: 99%
“…The constitutive relationship for couple stress fluids is presented by Stokes [3] in the analysis to derive the modified Reynolds equation in terms of a dimensionless couple stress parameter which represents the molecular length of the additives. The surface roughness is assumed to be single-sided, transverse, and sinusoidal [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Lin et.al. (18,19,20) studied the effect of viscosity pressure dependency (VPD) on the non-Newtonian squeeze film of circular plates and long partial journal bearings. They found that the couple stress fluid and the effect of pressure dependent viscosity causes an increase in the load carrying capacity and lengthens the squeeze film time.…”
Section: Introductionmentioning
confidence: 99%